Development of Boccia Sports Training Aid for People with Cerebral Palsy Disabilities Based on Bet (Boccia Equipment Tools) - Dayun Eryadi; Fajar Vidya Hartono; Iwan Setiawan (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
This study aimed to develop Boccia sports training aids for athletes with cerebral palsy disabilities in the Special Capital Region of Jakarta. The research used a research and development design with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants involved in this study included experts in testing and measurement, disability experts, Boccia coaches, and athletes with cerebral palsy disabilities. The final product was the Boccia Equipment Tools (BET), which consisted of a Boccia ramp, ball holder, small goal, high goal, stick helmet, bowling target, and point target. Expert validation results showed that BET was highly feasible, with feasibility, effectiveness, and training applicability scores of 82%, 82%, and 81%, respectively. The effectiveness test involving 17 athletes over 16 training sessions showed a significant improvement in Boccia throwing accuracy. The mean score increased from 13.94 in the pretest to 28.05 in the posttest, and the paired sample test showed a significant difference with p = 0.000. These findings indicate that BET is feasible and effective for supporting Boccia training, particularly in improving throwing accuracy among athletes with cerebral palsy disabilities. Future studies should examine the durability and long-term use of BET in wider training contexts.